Motor Vehicle Stocks, Scrappage, and Sales - Greenspan, Alan; Cohen, Darrel (The Review of Economics and Statistics, 1999)
This paper offers a framework for forecasting aggregate sales of new motor vehicles; this framework incorporates separate models for the change in the vehicle stock and for the rate of vehicle scrappage. Because this approach requires only a minimal set of assumptions about demographic trends, the state of the economy, consumer “preferences,” new vehicle prices and repair costs, and vehicle retirements, it is shown to be especially useful as a macroeconomic forecasting tool. In addition, this paper presents a new historical annual time-series estimate of motor vehicle stocks in the United States.